Opportunities for emergency medicine training in Australia. - Ryan, J M (1997)
Opportunities exist for graduates from the United Kingdom to undertake some of their emergency medicine training in Australia. Guidelines for graduates are presented on when to travel, how to find a position, what information one should obtain about a position, and how to acquire the necessary visa and medical registration. A successful visit takes some time to plan and requires cooperation between the negotiating parties. The graduate who undertakes training abroad can expect to benefit professionally and personally. The development of an international exchange network for trainees would streamline the process and broaden the appeal to graduates of completing some of their emergency medicine training in another country.